Telaah Unsur Delik Trading In Influence dalam Pembaharuan Hukum Pidana di Indonesia - Sheryn Lawrencya (Al-Adl : Jurnal Hukum, 2023)
Trading in influence acts that are non-mandatory offences has been regulated in the UNCAC, ratified by Law Number 7 of 2006 concerning the Ratification of the UNCAC. Based on cases in Indonesia, the act of Trading in Influence has developed in Indonesia but is considered a "bribery". Indonesia has not been able to ensnare influence trading actors based on the Corruption Law because there are no regulations governing it, resulting in legal uncertainty and a legal vacuum. So that there must be a difference between bribery and acts of trading in influence by examining the elements of the offence for reforming criminal Law, especially corruption. The normative juridical method uses literature or document studies and a statutory and comparative research approach. There is a proposed element of delict given based on a comparison between the UNCAC, French, Spanish and Belgian regulations, which is adjusted to a horizontal pattern with a trilateral relationship and is divided into two forms, active and passive. This act must be immediately regulated in positive Law in Indonesia, so there is no legal vacuum and uncertainty. It is hoped that the legislature and other authorized institutions can criminalize acts of trading in influence based on the values and principles of people's lives in Indonesia in the context of reforming the criminal Law.